Pengaruh Terapi Butterfly Hug Terhadap Tingkat Kecemasan Dalam Menjalani Skripsi Pada Mahasiswa Semester 6 Kelas 6A Reguler Prodi Keperawatan Universitas Indonesia Maju Tahun 2023 - Anis Yuliana; Marisca Agustina; Elvie Tresya (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
The thesis is an important element in higher education and reflects students' integrity in applying knowledge. However, the preparation of theses by final year students is often faced with various problems, especially high levels of anxiety. Anxiety can have a negative impact on physical and mental well-being. This research focuses on final year students who overcome anxiety during the preparation of their thesis by using Butterfly Hug therapy, a simple bilateral stimulation technique developed to increase feelings of calm. The aim of this research is to determine the effect of Butterfly Hug Therapy on the level of anxiety when undertaking a thesis in semester students. 6 Class 6A Regular Nursing Study Program, Advanced Indonesia University 2023 This research used a quasi-experimental one group pretest-posttest design without a control group. Data was collected through the Hamilton Rating Scale For Anxiety (HARS) questionnaire to measure students' anxiety levels before and after the Butterfly Hug therapy intervention. The aim of this research is to assess the effect of Butterfly Hug therapy on students' anxiety levels. The research results show a P-value of 0.000 (p < 0.05), indicating acceptance of the Ha hypothesis and rejection of H0. Thus, there was a significant change between the level of anxiety before and after administering the Butterfly Hug intervention. Conclusion Providing Butterfly Hug therapy had an effect on changes in the anxiety level of students in the 6th semester of class 6A of the Advanced Indonesia University Nursing Regular Study Program in 2023.